The mitochondrial genome sequences of eleven leafhopper species of Batracomorphus (Hemiptera: Cicadellidae: Iassinae) reveal new gene rearrangements and phylogenetic implications - Lu,Jikai; Wang,Jiajia; Dai,Renhuai; Wang,Xianyi (PeerJ, 2024)
Batracomorphus is the most diverse and widely distributed genus of Iassinae. Nevertheless, there has been no systematic analysis of the genome structure and phylogenetic relationships of the genus. To determine the characteristics of the mitogenomes of Batracomorphus species as well as the phylogenetic relationships between them, we sequenced and compared the mitogenomes of 11 representative Batracomorphus species. The results revealed that the mitogenomes of the 11 Batracomorphus species exhibited highly similar gene and nucleotide composition, and codon usage compared with other reported mitogenomes of Iassinae. Of these 11 species, we found that the mitogenomes of four species were rearranged in the region from trnI-trnQ-trnM to trnQ-trnI-trnM, whereas the remaining species presented a typical gene order. The topologies of six phylogenetic trees were in agreement. Eurymelinae consistently formed paraphyletic groups. Ledrinae and Evacanthinae formed sister taxa within the same clade. Similarly, Typhlocybinae and Mileewinae consistently clustered together. All phylogenetic trees supported the monophyly of Iassinae, indicating its evolutionary distinctiveness while also revealing its sister relationship with Coelidiinae. Notably, the nodes for all species of the genus Batracomorphus were well supported and these taxa clustered into a large branch that indicated monophyly. Within this large branch, four Batracomorphus species with a gene rearrangement (trnQ-trnI-trnM) exhibited distinctive clustering, which divided the large branch into three minor branches. These findings expand our understanding of the taxonomy, evolution, genetics, and systematics of the genus Batracomorphus and broader Iassinae groups.
Keywords: Batracomorphini; Iassinae; Leafhopper; Mitogenome; Phylogenetic analysis